The lactate metabolism and protein lactylation in epilepsy - Kuang, Xi; Chen, Shuang; Ye, Qingmei (Frontiers in Cellular Neuroscience, 2025)
Protein lactylation is a new form of post-translational modification that has recently been proposed. Lactoyl groups, derived mainly from the glycolytic product lactate, have been linked to protein lactylation in brain tissue, which has been shown to correlate with increased neuronal excitability. Ischemic stroke may promote neuronal glycolysis, leading to lactate accumulation in brain tissue. This accumulation of lactate accumulation may heighten neuronal excitability by upregulating protein lactylation levels, potentially triggering post-stroke epilepsy. Although current clinical treatments for seizures have advanced significantly, approximately 30% of patients with epilepsy remain unresponsive to medication, and the prevalence of epilepsy continues to rise. This study explores the mechanisms of epilepsy-associated neuronal death mediated by lactate metabolism and protein lactylation. This study also examines the potential for histone deacetylase inhibitors to alleviate seizures by modifying lactylation levels, thereby offering fresh perspectives for future research into the pathogenesis and clinical treatment of epilepsy.